2022
DOI: 10.1186/s12866-022-02620-z
|View full text |Cite
|
Sign up to set email alerts
|

Different rhizosphere soil microbes are recruited by tomatoes with different fruit color phenotypes

Abstract: Background To explore and utilize abundant soil microbes and their beneficial functions, the bacterial and fungal compositions in rhizospheres between red- and yellow-fruited tomato varieties were analyzed using high-throughput sequencing technique. Result Our results indicated that different soil microbes in rhizospheres of tomatoes were exactly recruited by different color fruit tomatoes. For the reasons as not only soil bacterial community, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Moreover, soil microbial biomass is also an important indicator for evaluating soil fertility [ 46 ], and the turnover of soil MBP could release inorganic phosphorus [ 52 ]. Additionally, soil phosphatases can be produced by plant roots and microbes in soil [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, soil microbial biomass is also an important indicator for evaluating soil fertility [ 46 ], and the turnover of soil MBP could release inorganic phosphorus [ 52 ]. Additionally, soil phosphatases can be produced by plant roots and microbes in soil [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing was performed using Illumina’s MiSeq PE250 and MiSeq PE300 platform (Shanghai Majorbio Biopharm Technology Co., Ltd., Shanghai, China). The processing and analysis of sequencing data were described previously in detail [ 45 , 46 ]…”
Section: Methodsmentioning
confidence: 99%
“…The ability of rhizosphere Streptomyces to enhance crop growth and stem ambient stress to promote crop health has variously reported in many crops(Hu et al, 2020;Kum and Ince, 2021;Pang et al, 2022). the maize apparently related with marginal differences among the habitats(Ni et al, 2023) and differ according to phylogenetic distance of crops(Chen et al, 2022;Lopes et al, 2023), in this case, the maize. The highest bacterial richness estimated via diversity indexes associated with Ma2R (6017) further consolidate the assertion that the rhizosphere in the southern part are relatively more nutritive for maize cultivation.…”
mentioning
confidence: 95%
“…Additionally, a mulberry variety resistant to bacterial wilt was reported to be enriched with fungal communities that can prevent the spread of soil-borne diseases, enhance plant drought resistance, and provide tolerance against biological or abiotic stresses [23]. Chen et al [24] found that different rhizospheric soil microbes are recruited by tomatoes with different fruit color phenotypes. Xiao et al [25] also found differences in rhizospheric microbes recruited by different watermelon phenotypes relating to rind color formation.…”
Section: Introductionmentioning
confidence: 99%